The internal and external factors that influence Intensive Advanced English students in their performance of the listening skill at the Foreign Language Department of the University of El Salvador during the semester I -2019 - Argumedo Escalante, Tania Lissette
The researchers conducted the descriptive research entitled “The internal and external factors that influence Intensive Advanced English students in their performance of the listening skill at the Foreign Language Department of the University of El Salvador during the semester I -2019.” Through this descriptive research, the researchers intended to identify the internal and external factors that hinder the development of the listening skill. To achieve this, the researchers carried out a series of steps. The descriptive research involved the researchers, two teachers, and fifty Advanced English students at the University of El Salvador, Semester I, 2019. To know the target population’s problem with regards to their listening skills, the researchers made use of different data collection instruments. After collecting and analyzing the data, the researchers provided the findings and conclusions. The results of this descriptive research showed that the internal and external factors might hinder the students’ development of their listening skills.